APPROXIMATION OF (ψ, β)-DIFFERENTIABLE FUNCTIONS BY WEIERSTRASS INTEGRALS - Kharkevych, Yurii I.; Kalchuk, Inna V.; Харкевич, Юрій Іліодорович; Кальчук, Інна Володимирівна (Ukrainian Mathematical Journal, 2007)
We obtain asymptotic equalities for upper bounds of approximations of functions from the classes Cψ β,∞ and Lψ β,1 by Weierstrass integrals.